Coordination of the two heads of myosin during muscle contraction - Lidke, Diane S. (National Academy of Sciences, 2002)
We have used luminescence resonance energy transfer between regulatory light chains (RLC) to detect structural changes within the dimeric myosin molecule in contracting muscle fibers. Fully functional scallop muscle fibers were prepared such that each myosin molecule contained a terbium-labeled (luminescent donor) RLC on one head and a rhodamine-labeled (acceptor) RLC on the other. Time-resolved luminescence energy transfer between the two heads increased upon the transition from relaxation (ATP) to contraction (ATP plus Ca) and increased further in rigor (no ATP). Combined with experiments on mutant RLCs labeled specifically at other sites, these results support a model in which the force-generating weak-to-strong transition causes one myosin LC domain to tilt through a 30° angle toward the other, thus acting as a coordinated lever arm.